Rora Sdn Bhd : Simple Easy Ice Cream Maker / Aiman Faris Zainur Amin ...[et al.] - Zainur Amin, Aiman Faris; Mordi, Muhammad Faizul Iqmal; Md Azman, Mohamad Fekry; Asatoh Delfrin, Muhammad Qmie Delfrin (2019)
Through these problems we manage to become more organize and mature in dealing with the problems that occur during our research. This business plan covers organization, marketing, operation, financial and training plan and any other information needed by a new entrepreneur as a guide to start this business. Lastly, to those who had involved and contributed directly or indirectly to this business plan we are very grateful to them for the effort and initiative that they have shown in our project until we successfully completed our business plan. I apologize to all other unnamed person who helped us various ways to complete this project and we hope this business plan report can give us little bit knowledge about Entrepreneurship world and fact about how to become a entrepreneur in future.